Republic of Kazakhstan : Financial Sector Assessment Program Update-Detailed Assessments and Updates of Financial Sector Standards and Codes. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper presents a Detailed Assessment and Updates of Financial Sector Standards and Codes for Kazakhstan. The assessment reveals that although Kazakhstan's banking system is liquid, there are significant variations from bank to bank, with the distinctions between the tenge and foreign exchange liquidity being quite important. An appropriate body of commercial law is in place, and both banks and the supervisory authority express general satisfaction with the functioning of the systems for registration of collateral and enforcement of security interests.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet